Practical Guide to Neurovascular Emergencies - Saliou, Guillaume; Theaudin, Marie; Join-Lambert Vincent, Claire; Souillard-Scemama, Raphaelle (Springer Paris : Imprint: Springer, 2014)
Modern vascular neurology, particularly in the emergency setting, often requires a great capacity for analysis and synthesis. Physicians who manage these patients must have acquired multidisciplinary skills, including a good knowledge of clinical neurology and medical imaging, but they may also need to be skilled in cardiology and intensive care. The initial clinical and imaging examinations play a decisive role in the management strategy. This book, written by neurologists and neuroradiologists, is designed to help all physicians involved in the management of neurovascular disease. The format and contents of this book, including the latest guidelines from learned societies, are designed to provide a succinct and practical guide. Although this book is particularly devoted to ischaemic stroke, other neurovascular diseases, especially haemorrhagic stroke, are also discussed. This book should constitute a valuable tool for everyday practice for all medical personnel involved in neurovascular disease. The French edition of this book received the 2013 Jean-François Ginestié Price, awarded by the French National Academy of Medicine.